2007
DOI: 10.1016/j.juro.2007.03.183
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function Outcomes in Patients Treated With Nephron Sparing Surgery for Bilateral Wilms Tumor

Abstract: When combined with adjuvant radiation and/or chemotherapy, nephron sparing surgery provides an opportunity to preserve renal function, while maintaining excellent long-term oncological outcomes for patients with bilateral Wilms tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 11 publications
0
34
0
1
Order By: Relevance
“…The understanding of the effect of NSS on renal functional outcomes is hampered by the lack of agreement between institutions on the definition of renal insufficiency as well as by the knowledge that some outcomes (e.g., hypertension) may improve following tumor resection, independent of the choice of surgical technique. Although serum creatinine appears to be consistently preserved in children undergoing NSS for BWTs, (and the need for dialysis appears to be nearly exclusive to patients in whom renal function is insufficient owing to large-volume parenchymal resection or underlying WT-associated syndromes) [63], a recent multicenter international study of children with UWTs treated with either NSS or radical nephrectomy identified specific tumor and patient characteristics associated with postsurgical changes in GFR. Children with large tumors had lower preoperative GFR than children with smaller tumors did, and patients with initial renal function placing them in chronic kidney disease stage 2 or greater were more likely to experience an increase in GFR following NSS [64].…”
Section: Functional Outcome After Nssmentioning
confidence: 99%
See 2 more Smart Citations
“…The understanding of the effect of NSS on renal functional outcomes is hampered by the lack of agreement between institutions on the definition of renal insufficiency as well as by the knowledge that some outcomes (e.g., hypertension) may improve following tumor resection, independent of the choice of surgical technique. Although serum creatinine appears to be consistently preserved in children undergoing NSS for BWTs, (and the need for dialysis appears to be nearly exclusive to patients in whom renal function is insufficient owing to large-volume parenchymal resection or underlying WT-associated syndromes) [63], a recent multicenter international study of children with UWTs treated with either NSS or radical nephrectomy identified specific tumor and patient characteristics associated with postsurgical changes in GFR. Children with large tumors had lower preoperative GFR than children with smaller tumors did, and patients with initial renal function placing them in chronic kidney disease stage 2 or greater were more likely to experience an increase in GFR following NSS [64].…”
Section: Functional Outcome After Nssmentioning
confidence: 99%
“…A German group found that in patients with BWTs, bilateral NSS was associated with a lower prevalence of postoperative hypertension than nephrectomy and contralateral NSS were [65]. The effect of the primary tumor [63] as well as of neoadjuvant and adjuvant therapies (chemotherapy and radiation) [55] on postsurgical blood pressure measurements cannot be predicted with certainty yet.…”
Section: Functional Outcome After Nssmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of favorable histology, bilateral WT is very good, with overall survival rates in excess of 80% being well documented [27,28]. Unfortunately, development of renal dysfunction in survivors of bilateral WT is a well-recognized complication.…”
Section: Bilateral Nonsyndromic Wtmentioning
confidence: 99%
“…Apart from this, it is also indicated in tumors involving a solitary kidney, bilateral renal involvement, and contralateral renal impairment [3]. Nephronsparing surgery should also be attempted in select patients with a solid renal mass in whom the contralateral kidney is threatened by local, systemic, or genetic conditions that may affect future function or the likelihood of subsequent contralateral tumors [14].…”
Section: Discussionmentioning
confidence: 99%